Effect of hulls on the digestibility of equine diet - Särkijärvi, Susanna; Saastamoinen, Markku (MTT, 2004)
In previous studies we have discovered that hulling of oats considerable improves its digestibility in equine diets (Särkijärvi & Saastamoinen 2003). However, hulling methods are variable and may lead to various outcomes. The more intensive the hulling is, the better the end product, but also the higher is the level of costs. In order to evaluate the appropriate hulling intensity, we wanted to study the effect of oat hulls on the diet digestibility. Eight mature Finnhorse mares were used in a study where effects of oat hulls on the apparent digestibility of nutrients was studied. Diets were based on dry hay and four different oat feeds (71:29 on dry matter basis). Oat feeds were based on hulled oats where four different amounts of oat hulls were added. The oat hull additions were: 1) 0% hulls, 2) 8% hulls, 3) 16% hulls and 4) 24% hulls. The last treatment represented the hull content of regular oats. Both, hulled oats and oat hulls, were first ground separately to a fine meal and then pressed into pellets, in order to prevent feed selection by horses. Treatments were assigned in a duplicated 4 x 4 Williams square design. A preliminary feeding of 16 days was followed by 5 day collection in each period. Faecal samples were taken twice a day during the collection period. Chromium mordanted straw was a marker for the estimation of digestibility. The inclusion of oat hulls did not affect digestibilities of diet nutrients statistically significantly. The digestibilities of nitrogen free extract and crude protein were slightly higher at 0% inclusion, and the digestibilities of crude fat and crude fibre were better for 16 and 24% inclusion rates, but as mentioned, the differences were not statistically significant. Probably the fine milling of the grain material has improved the digestibility of fibre of the oat hulls so tremendously, that the impairing effect of fibre did not show in diet digestibilities. Särkijärvi, S. & Saastamoinen, M. 2003. Feeding value of various prosessed oat grains. In: Ynze van der Honing et al. (eds.). Book of abstracts of the 54th Annual meeting of the EAAP. Wageningen: Wageningen Academic Publishers. p. 417.
Keywords: Ko; hevonen; kaura; ruokinta; digestibility; horse; oats; oat hulls; hulling